Tropical climate change and its impact on horticultural plants in Enrekang District, South Sulawesi, Indonesia - AMIR YASSI; EYMAL B. DEMMALLINO; HAIRUL RACHMAN SULTANI (Society for Indonesian Biodiversity, 2023)
Abstract.Yassi A, Demmallino EB, Sultani HR. 2023. Tropical climate change and its impact on horticultural plants in Enrekang District, South Sulawesi, Indonesia. Biodiversitas 24: 3073-3079. Global, regional, and local changes in climate are phenomenologically different and have distinct impacts on the horticultural and agricultural sectors. Therefore, this research aims to examine tropical climate change in South Sulawesi, Indonesia and analyze its impact on horticultural crops. Apost-positivistic interpretation framework of the case study tradition was used, while the location was determined by purposive sampling followed by comprehensive data collection. Data were analyzed using integrated techniques, and validity tests were carried outto assess thecredibility and reliability. The results indicated a local climate change marked by a differencein the pattern of distribution and intensity of extreme rainfall between 2015 and 2018. This was due toan increase in air temperature, which on average reached ±0.03731°C from the lowest of 22.50°C in 2011 to the highest of 23.12°C in 2020. In other words, it can be stated that the air temperature had increased by ±0.63°C in the last decade. The impact on various types of horticultural crops was marked by a decrease in the production of several kinds of Chinese cabbage,carrots, and green beans in 2015 as well asa very drastic reductionin potato crop production in 2018, while cabbage plants experienced a peak in production in 2018. Some types of horticultural crops such as shallots, cabbage and red chili began to stabilize and even increased their production in the aftermath of climate changeduring said period.